Community development masyarakat Gampong Lamgapang Aceh Besar dalam pemberdayaan ekonomi kreatif berbasis kearifan lokal (Community Development of Lamgapang Village, Aceh Besar in empowering creative economy based on local wisdom) - Hanafiah, Muhammad; Sulastri, S; Helmi, Teuku Zahrial (Buletin Pengabdian, 2022)
The activities of the Lamgapang Village community so far have done a lot of home industry businesses, but the results obtained are still relatively small, this is because the products produced are still unable to compete in the market. So that many people are still low-income and fall into the category of underprivileged families. The purpose of the activity is to increase community income based on developing Community Development activities for the Lamgapang Aceh Besar Community in Empowering Creative Economy Based on Local Wisdom. Provide motivational training and skills in plant cultivation using hydroponics and development of livestock health based on farmer empowerment. The method that will be used in this activity is using the Participatory Rural Appraisal approach. Partners participate in carrying out direct activities, especially in terms of production and analyzing problems in the field. The results of the service activities that have been carried out include: 1) The service team has succeeded in making hydroponic tools and planting hydroponic mustard plants; 2) For service activities based on livestock health, an examination of diseases in livestock and treatment for livestock has been carried out. The conclusion is that the community has been able to plant mustard greens using hydroponic tools and also the breeders already have the knowledge of how to raise livestock properly and correctly.